2005
DOI: 10.1080/00071660400023847
|View full text |Cite
|
Sign up to set email alerts
|

Soft wheat instead of hard wheat in pelleted diets results in high starch digestibility in broiler chickens

Abstract: (1) The aim of the experiment was to re-examine variations in digestibilities of food components in 3-week-old broiler chickens fed on pelleted diets based on wheats differing in lipase activity and hardness. Fourteen wheat (Triticum aestivum) samples, each from a different cultivar, were included at 550 g/kg in 14 different diets given to male Ross broiler chicks from 7 d of age. The other main ingredients consisted of soyabean meal (353 g/kg) and rapeseed oil (55 g/kg). A 15th diet containing durum wheat (Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 16 publications
4
13
1
Order By: Relevance
“…Although only small number of wheat samples was studied in this experiment, the results confirm the importance of research on wheat processing to better understand the interactions between processing and wheat chemical and quality characteristics when evaluating its feeding value for broilers. The proximate nutrient, polysaccharide and GE contents, and EH of the experimental wheat samples were in a similar range to those measured in other studies (Rose et al, 2001;Pirgozliev et al, 2003;Carre et al, 2005).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although only small number of wheat samples was studied in this experiment, the results confirm the importance of research on wheat processing to better understand the interactions between processing and wheat chemical and quality characteristics when evaluating its feeding value for broilers. The proximate nutrient, polysaccharide and GE contents, and EH of the experimental wheat samples were in a similar range to those measured in other studies (Rose et al, 2001;Pirgozliev et al, 2003;Carre et al, 2005).…”
Section: Discussionsupporting
confidence: 84%
“…However, there is inconsistence in the literature as some of the authors report responses on growth performance and nutrient availability to mash diets (Scott et al, 1998;Rose et al, 2001;Steenfeldt, 2001;Pirgozliev et al, 2003), others reported responses to pelleted diets (Wiseman et al, 2001;Carre et al, 2005). However, there is a lack of information on a direct comparison of feeding value of wheat with different chemical and quality characteristics, and the dietary form, thus more research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Negative relationships were also found between particle size or hardness of wheat and starch digestibility in growing chickens (Carré et al, 2002 and2005a). Besides this negative effect of coarse particles, it -E-mail: bernard.carre@tours.inra.fr was proposed that coarse particles could also be positive on digestion efficiencies in growing chickens because coarse particles might result in a larger gizzard and better control of gastric emptying with subsequent improved digestion efficiencies (Hetland et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…From 19 to 22 days of age, a digestive balance experiment was performed to determine individual AME n values and apparent digestibilities of dry matter and lipids, using a total collection method as previously described (Carré et al, 2005). Lipid content (Carré et al, 2002) of excreta was calculated using a relationship based on excreta gross energy and dry matter digestibility, fitted from the genetic selection programme (Mignon-Grasteau et al, 2004) ; R 2 5 0.895; n 5 2101, where L is the lipid content (%) of freeze-dried excreta; DMD the dry matter digestibility (%); and EGE the gross energy content (J/g) of freeze-dried excreta.…”
Section: Methodsmentioning
confidence: 99%
“…However, wheat for growing chicks was shown to result in a great variability in digestibility values (Steenfeldt, 2001;Carré et al, 2002). A part of this variability comes from differences in quality parameters of wheat samples, such as hardness and water-extract viscosity (Carré et al, 2002 and2005). Water-soluble arabinoxylans of wheat can give rise to highly viscous conditions in the small intestine, and hence to depressed nutrient absorption and broiler performance (Choct et al, 1995).…”
Section: Introductionmentioning
confidence: 99%